(untitled) (Philological Studies, 2019)
This article deals with a specific form of love, namely motherhood, defined as pure, unconditional, instinctive, painful and self-sacrificing. The cultural studies view advances from ancient mythology, prehistoric cave art, Neolithic figurines, onto medieval images, elongated gothic representations, and proportional Renaissance images, all the way to contemporary emancipatory forms, found in the modern literary, art and psychological interpretations of motherhood.